2002
DOI: 10.1046/j.1460-9592.2002.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pacemaker Lead Entrapment: Role of the Transesophageal Echocardiography

Abstract: Numerous complications induced by pacemaker electrodes have been reported. Although mild tricuspid regurgitation is a well-documented complication of transvenous right ventricular pacemaker leads secondary to abnormal valve coaptation, severe tricuspid regurgitation resultingfrom perforation of the tricuspid valve itself is a rare complication. This case report details a patient with severe tricuspid regurgitation secondary to impingement of the tricuspid valve by a permanent pacing lead that was diagnosed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Isolated case reports have been noted of entrapment of a PPM lead in the tricuspid apparatus during implantation, resulting in avulsion or laceration of the tricuspid valve leaflets upon removal of the PPM lead (6 -11) and case reports of perforation of a tricuspid valve leaflet by a PPM (Table 4) (12)(13)(14)(15)(16)(17)(18). Echocardiographic detection of tricuspid regurgitation in patients with a PPM has been reported (19).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated case reports have been noted of entrapment of a PPM lead in the tricuspid apparatus during implantation, resulting in avulsion or laceration of the tricuspid valve leaflets upon removal of the PPM lead (6 -11) and case reports of perforation of a tricuspid valve leaflet by a PPM (Table 4) (12)(13)(14)(15)(16)(17)(18). Echocardiographic detection of tricuspid regurgitation in patients with a PPM has been reported (19).…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism is asynchrony, resulting from abnormal right ventricle (RV) activation from a pacemaker. This may resolve if the patient returns to his/her intrinsic rhythm . Kim and colleagues demonstrated that TR after ICD or PPM implantation is not related to an increase in pulmonary artery pressure …”
Section: Mechanismmentioning
confidence: 99%
“…Compared with transthoracic echocardiography, transesophageal echocardiography may be potentially useful in identifying PPM-lead-related TR. 21,22 However, Lin et al reported that transesophageal echocardiography was able to visualize the PPM or ICD leads as a cause of TR in only 45% of patients, 7 and on that basis they recommended the use of 3-DE to identify intracardiac lead routes.…”
Section: Study Limitationsmentioning
confidence: 99%